Peningkatan Mutu Melalui Implementasi Manajemen PAKIS - Rismayani Rismayani; Nurhayati Nurhayati (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2021)
The problem of school quality is a classic problem that until now has encountered obstacles in the field. The various school management models that have been implemented sometimes do not match the character of the school and the conditions of the school. So in this school action research, it is tried to apply the PAKIS management model to improve the quality of the school in question. The purpose of this study was to reveal the impact of implementing PAKIS management with all its supporting factors at SD Negeri 6 Langsa City. This study uses the School Action Research (PTS) method by involving the Principal as a researcher, Teachers, Education Personnel, Students and parents of students and stakeholders. Data obtained through observation and interviews and then analyzed using the PTS step. This study concludes that the implementation of PAKIS management at SD Negeri 6 Langsa City is going well, the perceived impact of implementing PAKIS management can improve school achievement at SD Negeri 6 Langsa including: Increasing student achievement in both curricular and non-curricular fields, teacher achievement, achievement school and principal's performance. Supporting factors for implementing PAKIS school-based management in improving school achievement include support from school residents, community support and support from other institutions.